2017
DOI: 10.12776/ams.v23i1.879
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Heat Treatments on the Microstructure of Welded Api X70 Pipeline Steel

Abstract: Welding is one of the most important technological processes used in many branches of industry such us industrial engineering, shipbuilding, pipeline fabrication among others. Generally, welding is the preferred joining method and most common steel are weldable. This investigation is a contribution to some scientific works which have been done on welding of low carbon steel. This work, presents some heat treatments were used to alter the microstructure of base metal (BM), heat affected zone (HAZ) and weld meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 8 publications
2
11
0
Order By: Relevance
“…Many attempts have been made to analyse the microstructure of API X70 steel welded joints. However, there is a lack of a more systematic metallographic investigations comprising the base material, HAZ as well as weld metal with relation to mechanical properties [10][11][12][13][14][15][16][17][18][19][20]. Ghomashchi and co-workers [10] revealed that the microstructure of arc girth welded joint of the API X70 steel produced by the manual metal arc (MMA) welding with E6010 cellulosic electrodes are composed of Widmanstätten and acicular ferrites, lamellar pearlite and aggregated ferrite-carbide.…”
Section: Literature Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…Many attempts have been made to analyse the microstructure of API X70 steel welded joints. However, there is a lack of a more systematic metallographic investigations comprising the base material, HAZ as well as weld metal with relation to mechanical properties [10][11][12][13][14][15][16][17][18][19][20]. Ghomashchi and co-workers [10] revealed that the microstructure of arc girth welded joint of the API X70 steel produced by the manual metal arc (MMA) welding with E6010 cellulosic electrodes are composed of Widmanstätten and acicular ferrites, lamellar pearlite and aggregated ferrite-carbide.…”
Section: Literature Surveymentioning
confidence: 99%
“…The repairs have an influence on the HAZ width as well as on the grain size. The primary factors that affect the grain size are: temperature, holding time and microalloying elements [16]. Vega et al [17] found that an increase in the number of repairs may result in increasing the grain size.…”
Section: Literature Surveymentioning
confidence: 99%
“…The welded joints under exploitation conditions can be affected by the chemical heterogeneity or mechanical properties of base material, heat affected zone and weld metal. It has been concluded that by improving the microstructure of the HAZ, the properties of the welded joint can be improved [7]. Excessive heat input could result in a wide HAZ with low impact strength [8].…”
Section: Introductionmentioning
confidence: 99%
“…It has been concluded that by improving the microstructure of the HAZ, the properties of the welded joint can be improved [7].…”
Section: Controlling Of Hazmentioning
confidence: 99%